2020
DOI: 10.1002/admt.202000791
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel‐Based Additive Manufacturing of Lithium Cobalt Oxide

Abstract: 3D multicomponent metal oxides with complex architectures can enable previously impossible energy storage devices, particularly lithium‐ion battery (LIB) electrodes with fully controllable form factors. Existing additive manufacturing approaches for fabricating 3D multicomponent metal oxides rely on particle‐based or organic–inorganic binders, which are limited in their resolution and chemical composition, respectively. In this work, aqueous metal salt solutions are used as metal precursors to circumvent these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 52 publications
(72 reference statements)
0
22
0
Order By: Relevance
“…Yee et al fabricated metal oxides using metal-nitrate-containing aqueous photoresins, in a process that combined solution combustion synthesis (SCS) with VP. 215 The use of aqueous metal nitrate solutions as metal oxide precursors allowed for compositional versatility, and also compatibility with high-resolution VP techniques. This was demonstrated in the fabrication of piezoelectric zinc oxide microstructures with TPL using a zinc nitrate aqueous photoresin (Fig.…”
Section: In Situ Materials Synthesis To Advance Materials Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Yee et al fabricated metal oxides using metal-nitrate-containing aqueous photoresins, in a process that combined solution combustion synthesis (SCS) with VP. 215 The use of aqueous metal nitrate solutions as metal oxide precursors allowed for compositional versatility, and also compatibility with high-resolution VP techniques. This was demonstrated in the fabrication of piezoelectric zinc oxide microstructures with TPL using a zinc nitrate aqueous photoresin (Fig.…”
Section: In Situ Materials Synthesis To Advance Materials Developmentmentioning
confidence: 99%
“…217 Copyright 2020, Springer Nature. 215 SCS is a highly facile and versatile technique for the fabrication of metal oxide materials but is characterized by the rapid formation of a large amount of gases due to the oxidizing nature of the metal nitrates. 222 As a result, the LCO structures were macroporous despite the slow calcination process used.…”
Section: In Situ Materials Synthesis To Advance Materials Developmentmentioning
confidence: 99%
“…Among the expected challenges are: determining suitable precursor compounds and stoichiometries, obtaining rheological properties of the precursor resin that allow 3D printing of self-standing structures, and finding appropriate thermal post-processing conditions for the synthesis of battery materials and the elimination of non-electroactive components. Specifically focused on LIB, Yee et al [65] reported the synthesis of LiCoO2 via projection VPP. In this case, an aqueous PEGDA-based resin was loaded with Co(NO3)2.6H2O and LiNO3 in stoichiometric ratios, from which a hydrogel was printed and calcinated at 700 ºC (Fig.…”
Section: Iviii Precursor Approach: In Situ Synthesis Of the Electroactive Materials Upon Thermal Treatmentmentioning
confidence: 99%
“…In contrast, 3D printed electrodes require a certain micro-porosity, so that adequate electrolyte impregnation is allowed. To address this issue, Yee et al [65] worked on the tuning ratio of PEGDA-to-LiCoO2, and found that by increasing the lithium precursor, it was possible to increase the micro-porosity without excessively increasing the Ohmic impedance. Two other methods to promote micro-porosity are also mentioned.…”
Section: Iviii Precursor Approach: In Situ Synthesis Of the Electroactive Materials Upon Thermal Treatmentmentioning
confidence: 99%
See 1 more Smart Citation